Revisiting the assembly of amino ester-based benzene-1, 3, 5-tricarboxamides: chiral rods in solution. Issue 34 (31st March 2015) - Desmarchelier, Alaric; Raynal, Matthieu; Brocorens, Patrick; Vanthuyne, Nicolas; Bouteiller, Laurent
Abstract : Long rods and strong chiral amplification can be obtained from amino ester-based BTAs, by a suitable choice of structure and concentration. Abstract : Some benzene-1, 3, 5-tricarboxamide (BTA) monomers derived from (l ) α-amino esters self-assemble into long rods at millimolar concentrations, and display a strong chiral amplification effect. These rods are in competition with dimeric species.